2019
DOI: 10.1136/heartasia-2019-011223
|View full text |Cite
|
Sign up to set email alerts
|

Safety of performing transoesophageal echocardiography in patients with oesophageal varices

Abstract: IntroductionOesophageal varices (EV) are one of the complications of liver cirrhosis that carries a risk of rupture and bleeding. The safety of performing transesophageal echocardiography (TEE) in patients with pre-existing EV is not well described in literature. Therefore, this retrospective study has been conducted to evaluate the safety of preforming TEE in this group of patients.MethodsThe study population was extracted from the 2016 Nationwide Readmissions Data using International Classification of Diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…The only large database study showed no difference in rates of in-hospital bleeding between patients with esophageal varices who did or did not undergo TEE, with the caveat that patient characteristics and endpoints were based solely on diagnosis codes and were not clinically validated. (12) In line with prior reports, no patient in our study experienced a primary outcome of overt variceal hemorrhage. This finding is somewhat intuitive, as bleeding from varices generally is a consequence of vessel rupture from elevated portal pressure as opposed to external injury.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The only large database study showed no difference in rates of in-hospital bleeding between patients with esophageal varices who did or did not undergo TEE, with the caveat that patient characteristics and endpoints were based solely on diagnosis codes and were not clinically validated. (12) In line with prior reports, no patient in our study experienced a primary outcome of overt variceal hemorrhage. This finding is somewhat intuitive, as bleeding from varices generally is a consequence of vessel rupture from elevated portal pressure as opposed to external injury.…”
Section: Discussionsupporting
confidence: 88%
“…The only large database study showed no difference in rates of in‐hospital bleeding between patients with esophageal varices who did or did not undergo TEE, with the caveat that patient characteristics and endpoints were based solely on diagnosis codes and were not clinically validated. ( 12 )…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 We are concerned that the analysis by Hui and Leung likely overestimates the incidence of bleeding with diagnostic TEE by including non-operative therapeutic TEE cases as well as a large study that relied solely on International Classification of Diseases codes for outcome measures. 3 Moreover, in many instances, post-procedure blood loss appears to be principally related to underlying comorbid disease (e.g., cirrhosis) rather than the actual presence of varices, as evidenced by the authors' (and our own) finding that patients with cirrhosis and varices have no higher risk of bleeding than patients with cirrhosis and no varices. We also found no difference in bleeding outcomes (defined as hemoglobin decline by at least 2 g/ dL or blood transfusion within 48 hours of TEE) when endoscopy was performed prior to versus post TEE, arguing against the utility of routine pre-procedure endoscopic screening of cirrhotic patients.We wish to highlight that available data do not support the authors' suggestion that correction of coagulopathy prior to TEE is an effective way to reduce bleeding risk.…”
mentioning
confidence: 87%